URGENCY OF RELIGIOUS TOLERANCE IN PEACE EDUCATION: URGENSI TOLERANSI BERAGAMA DALAM PENDIDIKAN PERDAMAIAN - deden Syarif (Pergunu Jawa Barat, 2021)
The purpose of this study was to determine how peace education can foster religious tolerance. The research method used is qualitative where data collection is in a natural setting with the intention of interpreting the phenomena that occur. Research based on theoretical studies on peace education fosters a sense of religious tolerance.